AB0930 Cross-sectional analysis of the autonomic nervous system (heart rate variability): correlations with psychological dimensions in women with fibromialgia, rheumatoid arthritis and healthy controls. (15th June 2017) - Santiago, TL; Peixoto, D; Costa, C; Silva, JA Pereira da
Abstract : Background: Autonomic nervous system (ANS) dysfunction has been proposed to play a role in the pathophysiology and maintenance of rheumatic diseases, including fibromyalgia (FM) and rheumatoid arthritis (RA). Heart rate variability (HRV) analyses provide a quantitative marker of ANS activity. Some studies suggest an association between reduced HRV parameters and psychological dimensions, namely a negative emotional state. This led us to hypothesize an association between rheumatic diseases and higher sympathetic activity mediated by a negative emotional state. Objectives: To establish correlates between HRV parameters with rheumatic disease groups and psychological dimensions. Methods: Sixty women (FM, n =20; RA, n =20; healthy controls (Ct), n =20) completed a self-reported questionnaire addressing demographic characteristics, the Eysenck Personality Questionnaire, the Hospital Anxiety and Depression Scale, and the Beck Depression Inventory-II (BDI-II). HRV analysis was performed by photopletismography between 8:00 and 10:00am, after an overnight fast, in a sitting position, for 5-minutes. We obtained the time and frequency-domain indices of HRV, including SDNN (standard deviation of the NN intervals), RMSSD (root-mean square differences of successive R-R intervals), high frequency power (HF), low frequency power (LF) and very low frequency (VLF). LF/HF ratio reflects sympathetic to parasympathetic balance. Statistical analysis were performed considering: A) Rheumatic disease groups (FM/RA/Ct), and B) Psychological scores (irrespective of disease group): higher versus lower tertile in the personality questionnaires and score above (depression) versus below 20, in BDI-II. Between-groups comparisons were performed with Kruskal-Wallis test and analysis of covariance (age was adjusted during analyses), as appropriate. Results: Neuroticism, anxiety and depression scores were significantly higher in FM and RA patients compared with controls (p<0.05). However, no statistically significant difference was observed in HRV parameters between disease groups. No statistically significant difference was observed in HRV parameters between tertile groups for psychological dimensions, except for depression. The values of HF power (parasympathetic activity) were lower in the high depression group compared to the low depression group (p<0.05). The ratio of LF/HF was higher among the depression group than the control group (p<0.05). Conclusions: This study did not found significant differences in the HRV between the three rheumatic disease groups. The results confirm that depression is accompanied by dysfunction of the autonomic nervous system, specifically lower parasympathetic activity. These results suggest that psychological dimensions, namely depression, must be taken into account when evaluating the ANS and its impact in disease pathogenesis. Disclosure of Interest: None declared